Respostas
respondido por:
0
Oi Stefany
a)
-x² + 4x - 2 = 0
x² - 4x + 2 = 0
delta
d² = 16 - 8 = 8
d = 2√2
x1 = (4 + 2√2)/2 = 2 + √2
x2 = (4 - 2√2)/2 = 2 - √2
b)
x² + 3x - 2x = 0
x² + x = 0
x*(x + 1) = 0
x1 = 0
x2 = -1
.
a)
-x² + 4x - 2 = 0
x² - 4x + 2 = 0
delta
d² = 16 - 8 = 8
d = 2√2
x1 = (4 + 2√2)/2 = 2 + √2
x2 = (4 - 2√2)/2 = 2 - √2
b)
x² + 3x - 2x = 0
x² + x = 0
x*(x + 1) = 0
x1 = 0
x2 = -1
.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás